Lithium ion battery negative electrode material, preparation method thereof and lithium ion battery
Through the preparation of nano-scale silicon powder and carbon powder and titanium dioxide composite materials, combined with chiral ligand surface modification, the problems of low lithium storage and volume changes in the negative electrode material of lithium-ion batteries are solved, and high lithium storage capacity and cycling stability are achieved sex.
Patent Information
- Application Number
- CN202411354372.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The negative electrode material of existing lithium-ion batteries has low lithium storage capacity, and there is volume change in silicon during charging, resulting in material structure damage, mechanical powdering and rupture of SEI film, affecting battery capacity and cycling performance.
Using nano-scale silicon powder and carbon powder and titanium dioxide composite materials, the surface modification of chiral ligands and the use of titanium dioxide is used to inhibit the volume expansion of the silicon material, and a stable lithium-ion battery negative electrode material is formed through calcination treatment.
The lithium storage capacity of the lithium battery negative electrode material is significantly improved, cycling stability and stable bonding to the current collector are ensured, and capacity attenuation and deterioration of cycling performance caused by volume changes are avoided.
Smart Images

Figure BDA0005063174750000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of lithium ions between the positive and negative electrodes to work. + Insertion and deinsertion back and forth between the two electrodes: During charging, Li + It is deintercalated from the positive electrode and then embedded into the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; the opposite is true during discharge. Lithium-ion batteries are widely used in new energy vehicles and other fields due to their excellent performance such as high operating voltage, high energy density, long life, wide application temperature range, and no memory.
[0003] In the related art, the negative electrode material of lithium-ion batteries is generally graphite. However, the capacity of the current mainstream graphite negative electrode material is close to its theoretical gram capacity of 372mAh / g. As far as the material itself is concerned, it is difficult to further increase the gram capacity. Therefore, seeking a negative electrode material for lithium-ion batteries with a higher gram capacity has become the key to the development of battery products with larger specific capacity and higher energy density. Silicon has attracted the attention of many researchers because of its theoretical lithium storage capacity of 4200mAh / g, low lithium desorption / insertion potential, abundant reserves and low cost. However, silicon has not been widely used in the negative electrode of lithium-ion batteries at present. The main reason is that silicon has serious volume changes during the process of lithium desorption / insertion. This characteristic causes the battery capacity to decay and the cycle performance to deteriorate in two aspects when used as a negative electrode material. On the one hand, the destruction of the material structure and mechanical pulverization cause the separation of the negative electrode material and the current collector, which physically reduces the battery capacity and cycle performance; on the other hand, the expansion and contraction of the volume cause the continuous rupture and reconstruction of the SEI film, which continuously consumes the active material, causing the battery capacity decay and cycle performance deterioration and other adverse effects. Therefore, silicon as a negative electrode material for batteries does not yet have the conditions for large-scale application. However, combined with comprehensive technical research on graphite negative electrode materials and the characteristics of silicon's high lithium storage capacity, silicon / carbon composite materials have been favored by many researchers. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium ion battery negative electrode material and a preparation method thereof, as well as a lithium ion battery having the lithium ion battery negative electrode material, so as to solve the problems of low lithium storage capacity of existing lithium ion battery negative electrode materials, volume change of silicon during charging, and separation of the negative electrode material from the current collector easily caused by long-term charge and discharge cycles.
[0005] In order to achieve the above object, the present invention provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps:
[0006] Nano-scale silicon powder, carbon powder, chiral ligand and a first dispersant are mixed and ground to obtain a silicon / carbon composite precursor, the silicon / carbon composite precursor is heat-treated in an inert gas, and after cooling, the silicon / carbon composite material is ground to obtain a silicon / carbon composite material; a second dispersant and a surfactant are added to a titanium-containing compound to obtain a titanium dioxide precursor solution, the silicon / carbon composite material is dispersed in the titanium dioxide precursor solution to obtain a silicon / carbon / titanium dioxide composite precursor, and the silicon / carbon / titanium dioxide composite precursor is calcined to obtain the lithium-ion battery negative electrode material.
[0007] Preferably, the chiral ligand is selected from at least one of a chiral amino acid, a chiral acid, a chiral amine and a chiral cyclic compound;
[0008] Preferably, the weight ratio of the nano-scale silicon powder to the chiral ligand is 1:0.5-0.8.
[0009] Preferably, the particle size of the nano-scale silicon powder is 10-50 nm;
[0010] The carbon powder is graphite, and the particle size of the graphite is preferably 1-10 μm;
[0011] The inert gas is selected from at least one of nitrogen, argon and helium.
[0012] Preferably, the titanium-containing compound is an organic compound or an inorganic compound containing titanium.
[0013] Preferably, the first dispersant and the second dispersant are each independently selected from at least one of ethanol, ethylene glycol and propanol.
[0014] Preferably, the heat treatment is a heat preservation treatment at a temperature of 550-620° C. for 6-7 hours.
[0015] Preferably, the calcination temperature is 500-600°C.
[0016] Preferably, the preparation method further comprises drying the silicon / carbon / titanium dioxide composite precursor before the calcination, and grinding the calcined product after the calcination;
[0017] Preferably, the drying conditions include: drying temperature of 45-55°C, drying time of 12-24h;
[0018] Preferably, the particle size of the lithium battery negative electrode material obtained after the grinding treatment is 10-30 μm.
[0019] The present invention also provides a negative electrode material for a lithium ion battery, and the negative electrode material for a lithium ion battery is prepared by the above-mentioned preparation method.
[0020] The present invention also provides a lithium ion battery, wherein the negative electrode active material of the lithium ion battery is the above-mentioned lithium ion battery negative electrode material.
[0021] According to the above technical means, the present invention significantly improves the lithium storage capacity of the negative electrode material of the lithium battery by adding nano-scale silicon powder with a theoretical capacity of up to 4200mAh / g into the carbon powder, and further modifies the surface of the nano-scale silicon powder by a chiral ligand so that the surface of the nano-scale silicon powder forms chiral characteristics. The inventors found that through this technical means, the volume expansion of the silicon material is effectively suppressed, thereby effectively solving the problem of serious volume expansion of the silicon material during the charging process of the lithium-ion battery; in addition, since titanium dioxide has the characteristic of low ductility, it can suppress the volume change inside the pore to a certain extent, thereby ensuring that the lithium-ion negative electrode active material provided by the present invention has good cycle stability. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] The invention provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps: mixing nanometer-scale silicon powder, carbon powder, a chiral ligand and a first dispersant, grinding the mixture to obtain a silicon / carbon composite precursor, heat-treating the silicon / carbon composite precursor in an inert gas, and grinding the mixture after cooling to obtain a silicon / carbon composite material; adding a second dispersant and a surfactant to a titanium-containing compound to obtain a titanium dioxide precursor solution, dispersing the silicon / carbon composite material in the titanium dioxide precursor solution to obtain a silicon / carbon / titanium dioxide composite precursor, and calcining the silicon / carbon / titanium dioxide composite precursor to obtain the negative electrode material for a lithium ion battery.
[0024] In the technical solution provided by the present invention, the lithium storage capacity of the negative electrode material of the lithium battery can be significantly improved by adding nano-scale silicon powder to the carbon powder, and the surface of the nano-scale silicon powder is further modified by a chiral ligand so that the surface of the nano-scale silicon powder forms chiral characteristics. The inventors found that the volume expansion of the silicon material is effectively suppressed by this technical means, thereby effectively solving the problem of serious volume expansion of the silicon material during the charging process of the lithium-ion battery; in addition, since titanium dioxide has the characteristic of low ductility, it can suppress the volume change inside the pore to a certain extent, thereby ensuring that the lithium-ion negative electrode active material provided by the present invention has good cycle stability.
[0025] In addition, after the negative electrode material of the lithium ion battery provided by the present invention is coated on the current collector, since the volume change rate of the titanium dioxide material is low, and the chiral properties imparted to the surface of the nano-scale silicon powder can also significantly suppress the volume expansion problem of the silicon material during the charge and discharge process, the negative electrode material provided by the present invention can always maintain stable adhesion with the current collector, so that the negative electrode material of the lithium ion battery can further suppress the problem of separation from the current collector caused by the volume change of the silicon-carbon composite material, thereby ensuring the stability and reliability of the lithium ion battery.
[0026] According to the preparation method provided by the present invention, the function of the chiral ligand is to form a chiral environment on the surface of nano-scale silicon powder, thereby giving it chiral characteristics. The chiral ligand is selected from at least one of chiral amino acids, chiral acids, chiral amines and chiral cyclic compounds; wherein the chiral amino acids can be L-glycine, L-alanine, etc., which have natural chiral characteristics and can be attached to the surface of nano-scale silicon powder, so that the surface of nano-silicon has chirality; the chiral acid can be specifically chiral lactic acid or chiral citric acid; the chiral amine can be specifically phenylethylamine or chiral polyamine, which can specifically interact with the surface of nano-scale silicon powder through hydrogen bonds to achieve attachment to the surface of nano-scale silicon powder; the chiral cyclic compound can be specifically chiral cyclopentene compounds, which are attached to the surface of nano-scale silicon powder through π-π interactions.
[0027] In the present invention, the weight ratio of the nano-scale silicon powder to the chiral ligand has an important influence on the final formation of suitable chiral characteristics on the surface of the nano-scale silicon powder. The inventors have experimentally verified that excessive or insufficient amounts of chiral ligands are not conducive to the stability and reliability of the chiral characteristics. Specifically, in the technical solution provided by the present invention, the weight ratio of the nano-scale silicon powder to the chiral ligand is 1:0.5-0.8.
[0028] According to the present invention, silicon has a theoretical lithium storage capacity of up to 4200mAh / g. In order to improve the contact effect with the electrolyte and increase the electrochemical reaction rate, the present invention preferably uses nano-scale silicon powder; in addition, the use of nano-scale silicon powder can also alleviate the problem of size change of silicon during the charging and discharging process to a certain extent, thereby achieving the effect of improving the cycle stability. However, the particle size of nano-scale silicon powder is not the smaller the better, because nano-scale silicon powder with too small a particle size is more likely to agglomerate, which will affect its performance; in addition, nano-scale silicon powder with too small a particle size also has the defects of poor mechanical properties and high manufacturing cost. Therefore, in the technical solution of the present invention, the particle size of the nano-scale silicon powder is 10-50nm.
[0029] It should be noted that in the present invention, the nano-scale silicon powder can be obtained by any suitable method, such as ball milling micron-scale silicon powder to prepare nano-scale silicon powder. Specifically, for example, polycrystalline silicon with a D50 of 5-10 μm and zirconium oxide balls are added to a zirconium oxide ball mill according to a certain mass ratio (for example, a mass ratio of 1:5), and n-hexane is used as a solvent. After 30 minutes of forward rotation at a speed of 200 r / min, the mill is allowed to stand for 5 minutes. After the standing is completed, the mill is reversed at a speed of 200 r / min for 30 minutes, and then allowed to stand for 5 minutes. Then, the above operation is repeated until the total ball milling time is 12 hours. After the ball milling treatment, the zirconium oxide balls and the silicon powder are separated through a sieve to obtain nano-scale silicon powder.
[0030] According to the present invention, the present invention does not specifically limit the type of the carbon powder, for example, it can be graphite. When the graphite raw material is selected, the particle size of the graphite is preferably 1-10 μm.
[0031] According to the present invention, the role of the inert gas is to construct a protective gas atmosphere. The inert gas can be selected from conventional ones in the art, for example, it can be at least one of nitrogen, argon and helium.
[0032] According to the present invention, the titanium-containing compound is an organic compound or an inorganic compound containing titanium. As an organic compound containing titanium, for example, tetrabutyl titanate may be used; as an inorganic compound containing titanium, for example, titanic acid, titanate, titanium tetrachloride or titanium trichloride may be used. It is understood that in the present invention, the titanium-containing compound used as a raw material for preparation may be used alone or in combination of multiple titanium-containing compounds.
[0033] The surfactant is a block copolymer surfactant, for example, a polyethylene-butadiene copolymer or a styrene-butadiene-chloropropylene copolymer. In the present invention, by mixing a block copolymer surfactant into the titanium-containing compound, the uniform dispersion of the silicon / carbon composite material in the titanium dioxide precursor solution can be promoted, and then after calcination, the silicon / carbon composite material can be uniformly dispersed in the inner pore structure of titanium dioxide, thereby ensuring the overall electrochemical performance of the negative electrode material of the lithium ion battery.
[0034] According to the present invention, the first dispersant and the second dispersant function to achieve dispersion. In the present invention, the first dispersant and the second dispersant are each independently selected from at least one of ethanol, ethylene glycol, and propanol.
[0035] According to the present invention, the heat treatment is a heat preservation treatment at a temperature of 550-620° C. for 6-7 hours.
[0036] According to the present invention, the temperature of the calcination treatment is 500-600°C.
[0037] According to the present invention, the preparation method also includes drying the silicon / carbon / titanium dioxide composite precursor before the calcination treatment, and grinding the calcined product after the calcination treatment; further, the conditions of the drying treatment include: a drying temperature of 45-55°C, a drying time of 12-24h; and a particle size of the lithium battery negative electrode material obtained after the grinding treatment is 10-30μm.
[0038] The present invention also provides a negative electrode material for a lithium ion battery, and the negative electrode material for a lithium ion battery is prepared by the above-mentioned preparation method.
[0039] The present invention also provides a lithium ion battery, wherein the negative electrode active material of the lithium ion battery is the above-mentioned lithium ion battery negative electrode material.
[0040] The following is a further description of the method for preparing the negative electrode material for a lithium ion battery provided by the present invention through specific examples.
[0041] Example 1
[0042] A method for preparing a negative electrode material for a lithium ion battery comprises the following steps:
[0043] S1: Take polycrystalline silicon with a D50 of 6μm and zirconia balls in a mass ratio of 1:5 and add them to a zirconia ball mill. Use n-hexane as the solvent, rotate forward at 200r / min for 30min and then let it stand for 5min. After the standing is completed, reverse at 200r / min for 30min, and then let it stand for 5min. Repeat the above operation until the total ball milling time is 12h. After ball milling, separate the zirconia balls and silicon powder through a sieve to obtain 25nm nano-scale silicon powder.
[0044] S2: Take 800g of graphite powder with a particle size of 5μm, then add 200g of nano-scale silicon powder obtained in step S1, 150g of chiral lactic acid and 1200mL of anhydrous ethanol, and then perform ball milling at a rotation speed of 300r / min for 30min to obtain a silicon / carbon composite precursor.
[0045] S3: The silicon / carbon composite precursor obtained in step S2 is placed in a high-temperature furnace, and after nitrogen protection is introduced, it is kept at 600°C for 7 hours, then cooled to 250°C at a rate of 5°C / min, and then naturally cooled to room temperature. After crushing and screening, a silicon / carbon composite material is obtained.
[0046] S4: 300 g of tetrabutyl titanate, 200 mL of anhydrous ethanol and 20 g of polyethylene-butadiene copolymer were mixed and rapidly stirred to obtain a titanium dioxide precursor solution;
[0047] S5: adding the silicon / carbon composite material obtained in step S3 to the titanium dioxide precursor solution in step S4, and dispersing the mixture by a high-speed disperser to obtain a silicon / carbon / titanium dioxide composite precursor;
[0048] S6: The silicon / carbon / titanium dioxide composite precursor obtained in step S5 is placed in a drying oven and dried at 50°C for 18 hours, followed by calcination in an air furnace at a temperature of 550°C. The calcined material is then ball-milled and sieved to obtain a lithium battery negative electrode material with a particle size of 20 μm.
[0049] Example 2
[0050] The method steps for preparing the negative electrode material for a lithium ion battery in this embodiment are basically the same as those in Example 1, except that in step S1, the ball milling time is controlled so that 10 nm nano-scale silicon powder can be sieved through the mesh, and the other conditions remain unchanged, and finally a lithium battery negative electrode material with a particle size of 20 μm is obtained.
[0051] Example 3
[0052] The method steps for preparing the negative electrode material for a lithium ion battery in this embodiment are basically the same as those in Example 1, except that in step S1, the ball milling time is controlled so that 50 nm nano-scale silicon powder can be sieved through the mesh, and the other conditions remain unchanged, and finally a lithium battery negative electrode material with a particle size of 20 μm is obtained.
[0053] Example 4
[0054] The steps of the method for preparing the negative electrode material for a lithium ion battery in this embodiment are basically the same as those in Example 1, except that in step S2, the amount of chiral lactic acid added is adjusted to 100 g, and the other conditions remain unchanged, and finally a negative electrode material for a lithium battery with a particle size of 20 μm is obtained.
[0055] Example 5
[0056] The steps of the method for preparing the negative electrode material for a lithium ion battery in this embodiment are basically the same as those in Example 1, except that in step S2, the amount of chiral lactic acid added is adjusted to 160 g, and the other conditions remain unchanged, and finally a negative electrode material for a lithium battery with a particle size of 20 μm is obtained.
[0057] Example 6
[0058] The steps of the method for preparing the negative electrode material for a lithium ion battery in this embodiment are basically the same as those in Example 1, except that in step S2, 150 g of chiral lactic acid is adjusted to 150 g of L-alanine; the other conditions remain unchanged, and finally a lithium battery negative electrode material with a particle size of 20 μm is obtained.
[0059] Comparative Example 1
[0060] The steps of the method for preparing the negative electrode material for a lithium ion battery in this comparative example are basically the same as those in Example 1, except that chiral lactic acid is not added in step S2, and other conditions remain unchanged, and finally a negative electrode material for a lithium battery with a particle size of 20 μm is obtained.
[0061] Comparative Example 2
[0062] The steps of the method for preparing the negative electrode material for a lithium ion battery in this comparative example are basically the same as those in Example 1, except that in step S1, the ball milling time is controlled to be able to be sieved to obtain 5nm nano-scale silicon powder, and the other conditions remain unchanged, and finally a lithium battery negative electrode material with a particle size of 20μm is obtained.
[0063] Comparative Example 3
[0064] The steps of the method for preparing the negative electrode material for a lithium ion battery in this comparative example are basically the same as those in Example 1, except that in step S1, the ball milling time is controlled to be able to be sieved through the mesh to obtain 90nm nano-scale silicon powder, and the other conditions remain unchanged, and finally a lithium battery negative electrode material with a particle size of 20μm is obtained.
[0065] Comparative Example 4
[0066] The steps of the method for preparing the negative electrode material of a lithium ion battery in this comparative example are basically the same as those in Example 1, except that sodium dodecyl sulfate is added in step S4 to replace the polyethylene-butadiene copolymer, and the rest remains unchanged, and finally a negative electrode material of a lithium battery with a particle size of 20 μm is obtained.
[0067] The present invention uses a half-cell test method to evaluate the performance of the prepared lithium-ion battery negative electrode material. Specifically, the lithium-ion battery negative electrode material prepared in the above embodiments and comparative examples is used as a negative electrode active material to prepare a slurry, and the slurry ratio is: negative electrode active material: Super p: PAALi = 90:3:7 (mass ratio), and then the prepared slurry is coated on a copper foil, and dried under vacuum conditions for 12 hours to form a negative electrode sheet. The electrolyte is purchased commercially, PE is used as a diaphragm, and a lithium sheet is used as a counter electrode. It is assembled in a glove box to form a half-cell. A constant current charge and discharge test is carried out in the LAND battery test system, and the charge and discharge voltage during the test is limited to 0.005-1.5V. A computer-controlled charge and discharge cabinet is used for data acquisition and test control.
[0068] Table 1: Performance of negative electrode materials for lithium ion batteries in Examples 1-6 and Comparative Examples 1-4
[0069]
[0070] Based on the above test data, it can be clearly seen that the lithium ion battery negative electrode material prepared based on the method provided by the present invention has higher gram capacity, first coulombic efficiency and cycle performance.
[0071] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode material for a lithium ion battery, characterized in that: The following steps are involved: The nano-scale silicon powder, carbon powder, chiral ligand and first dispersant are mixed and then ground to obtain a silicon / carbon composite precursor, the silicon / carbon composite precursor is heat-treated in an inert gas, and after cooling, ground to obtain a silicon / carbon composite material; A second dispersant and a surfactant are added to the titanium-containing compound to obtain a titanium dioxide precursor solution, the silicon / carbon composite material is dispersed in the titanium dioxide precursor solution to obtain a silicon / carbon / titanium dioxide composite precursor, and the silicon / carbon / titanium dioxide composite precursor is calcined to obtain the lithium-ion battery negative electrode material.
2. The preparation method according to claim 1, characterized in that: The chiral ligand is selected from at least one of a chiral amino acid, a chiral acid, a chiral amine and a chiral cyclic compound; Preferably, the weight ratio of the nano-scale silicon powder to the chiral ligand is 1:0.5-0.
8.
3. The preparation method according to claim 1, characterized in that: The particle size of the nano-scale silicon powder is 10-50nm; The carbon powder is graphite, and the particle size of the graphite is preferably 1-10 μm; The inert gas is selected from at least one of nitrogen, argon and helium.
4. The preparation method according to claim 1, characterized in that: The titanium-containing compound is an organic compound or an inorganic compound containing titanium.
5. The preparation method according to claim 1, characterized in that: The first dispersant and the second dispersant are each independently selected from at least one of ethanol, ethylene glycol, and propanol.
6. The preparation method according to claim 1, characterized in that: The heat treatment is carried out at a temperature of 550-620° C. for 6-7 hours.
7. The preparation method according to claim 1, characterized in that: The calcination temperature is 500-600°C.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method further comprises drying the silicon / carbon / titanium dioxide composite precursor before the calcination, and grinding the calcined product after the calcination; Preferably, the drying conditions include: drying temperature of 45-55°C, drying time of 12-24h; Preferably, the particle size of the lithium battery negative electrode material obtained after the grinding treatment is 10-30 μm.
9. A negative electrode material for a lithium ion battery, characterized in that: The lithium-ion battery negative electrode material is prepared by the preparation method described in any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The negative electrode active material of the lithium ion battery is the negative electrode material of the lithium ion battery according to claim 9.
Citation Information
Patent Citations
Method for preparing titanium oxide doped silicon carbon lithium ion battery negative electrode material by combining sanding with spray drying
CN115498149A
Lithium battery negative electrode material, lithium battery and preparation method
CN116230895A
Preparation method of nanometer silicon battery negative electrode material
CN117976892A
